2014
DOI: 10.1111/cge.12415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a unique, specialist psychiatric genetic counseling clinic: uptake and impact

Abstract: Background-People with psychiatric disorders and their family members have expressed interest in receiving genetic counseling (GC). In February 2012, we opened the first (to our knowledge) specialist psychiatric GC clinic of its kind, for individuals with non-syndromic psychiatric disorders and their families. Prior to GC and at a standard one-month follow-up session, clinical assessment tools are completed, specifically, the GC outcomes scale (GCOS, which measures empowerment, completed by all clients) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
166
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(178 citation statements)
references
References 38 publications
8
166
2
2
Order By: Relevance
“…Optimal genetic counseling incorporates both education and encouragement, assisting patients in embracing their autonomy and understanding what sort of control they might have in managing their symptoms [28]. Indeed, a specialized psychiatric genetic counseling clinic was shown in a naturalistic study to be successful in increasing patients’ sense of empowerment and self-efficacy [42]. A small randomized trial of genetic counseling for people with serious mental disorders showed equivalent gains in knowledge in patients given educational material to read, but improved accuracy of risk perception as compared with patients on a waiting list; there were no significant differences among the groups on stigma or perceived control [43].…”
Section: Addressing the Ethical Challengesmentioning
confidence: 99%
“…Optimal genetic counseling incorporates both education and encouragement, assisting patients in embracing their autonomy and understanding what sort of control they might have in managing their symptoms [28]. Indeed, a specialized psychiatric genetic counseling clinic was shown in a naturalistic study to be successful in increasing patients’ sense of empowerment and self-efficacy [42]. A small randomized trial of genetic counseling for people with serious mental disorders showed equivalent gains in knowledge in patients given educational material to read, but improved accuracy of risk perception as compared with patients on a waiting list; there were no significant differences among the groups on stigma or perceived control [43].…”
Section: Addressing the Ethical Challengesmentioning
confidence: 99%
“…Empirical studies suggest that when the role of genetics is explained to individuals with psychiatric disorders and their families in the context of the role of the environment (i.e. genetic counselling), outcomes are positive (Austin and Honer, 2008), internalized stigma can decrease (Costain et al, 2014a, 2014b; Hippman, 2016), and empowerment increases (Inglis et al, 2015). …”
mentioning
confidence: 99%
“…Given the pressures involved in these emotional decisions, Dr. Bowers should emphasize ahead of referral that genetic counseling offers significant psychotherapeutic and educational value and does not commit Mrs. Castle to genetic testing [11]. Mrs. Castle should expect genetic counseling to contextualize her risk and provide an informative, nondirective discussion of the implications of the disease.…”
Section: Figure 2 Genetic Testing Decision Treementioning
confidence: 99%